Blood culture: Profi le of bacterial infections of newborns admitted from maternity - Bennaoui F; El Idrissi Slitine N; Benbahia A; Soraa N; Maoulainine F.M.R (Open Journal of Bacteriology - Peertechz Publications, 2018)
Blood culture provides an undeniable ideal aid in the diagnosis of neonatal infection, its result is reliable. The aim of our work was to evaluate the bacteriological profi le of bacteraemias, newborns admitted from the hospital maternity IBN TOFAIL. A retrospective study on the cases of newborns hospitalized in the neonatal care unit, Mohamed VI University Hospital, Marrakech, originating from the delivery room of the IBN TOFAIL Gynecology and Obstetrics Department, during a period of 6 months From June to November 2016. 125 blood cultures were collected, 43 were positive, representing an overall positivity rate of 34.4%. Positive blood cultures by coagulase-negative staphylococcal were 27. The other bacteremias were 16, represented by multiresistant germs, with the predominance of Klebsiella pneumoniae (5 cases), Acenitobacter Baumanii (4 cases) and Serratia marcescens in 3 cases. Bacteremia on admission; especially to multidrug-resistant germs, presents a major problem of therapeutic management. We insist on the need to improve the conditions of delivery in our context and to develop new diagnostic and therapeutic strategies.